Stress Fracture of Non-Reinforced Concrete: Analytical Solutions and Experimental Development - Pastran, Carlos; Camargo, Manuel; Maldonado-Villa, Jorge (Migration Letters, 2023)
To analyze the behavior of non-reinforced concrete subjected to stresses, the analytical solutions proposed by Griffith and Irwin regarding the mechanics of linear elastic fracture for brittle materials were evaluated. These analyses involve criteria such as plastic deformation, cohesive force, fracture effort, elastic potential energy, and critical energy release rate. These analytical solutions were compared with experimental results carried out during the investigation and other authors’ results. In this way, it was possible to establish trends in terms of mechanical behaviors. It was shown that the Griffith analytical solution, based on which was formulated by the Irwin solution, generates a greater correlation with the actual behavior of concrete specimens at the specified design resistance. Finally, Griffith’s analytical solution was adjusted based on the flexural stress tests. The mix to manufacture the cylinders and test beams was designed according to the procedures of the American Concrete Institute, ACI Committee 211 and the Road Note Laboratory (RNL).